2022
DOI: 10.1038/s41598-022-22845-2
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and species facilitation affect the recruitment of macroalgal marine forests

Abstract: Marine forests are shrinking globally due to several anthropogenic impacts including climate change. Forest-forming macroalgae, such as Cystoseiras.l. species, can be particularly sensitive to environmental conditions (e.g. temperature increase, pollution or sedimentation), especially during early life stages. However, not much is known about their response to the interactive effects of ocean warming (OW) and acidification (OA). These drivers can also affect the performance and survival of crustose coralline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 103 publications
1
11
0
Order By: Relevance
“…Cystoseira s.l. species will have no choice but to try to adapt to the multiple impacts of climate change that are already affecting most marine ecosystems [ 108 ], but regulation of herbivorous fish populations must be considered an extremely urgent step to be implemented in areas of the Mediterranean where they have been shown to play a major role in the regression of brown algal forests.…”
Section: Discussionmentioning
confidence: 99%
“…Cystoseira s.l. species will have no choice but to try to adapt to the multiple impacts of climate change that are already affecting most marine ecosystems [ 108 ], but regulation of herbivorous fish populations must be considered an extremely urgent step to be implemented in areas of the Mediterranean where they have been shown to play a major role in the regression of brown algal forests.…”
Section: Discussionmentioning
confidence: 99%
“…Significant reductions in settlement of various Cystoseira s.l . species have been observed after a few days of exposure to abnormally high temperatures (Capdevila et al, 2015; Verdura et al, 2018; Monserrat et al, 2022). Moreover, photosynthetic efficiency of adults was also proven to be reduced after 2 weeks of exposures at 28°C, while after 25 days even the tissues were damaged in the population of Port de la Selva (Verdura et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments have shown that sea level rise in the region may expose intertidal macroalgal populations to grazing by rabbitfish, leading to reduced algal cover in very shallow waters in the long term [ 97 ]. Further, the species forming the forests may be vulnerable to the effects of ocean warming and ocean acidification [ 26 , 27 ]. For instance, Gongolaria rayssiae , a species endemic only to Israel and Lebanon, completely loses its branches in early summer and its optimum temperature matches spring temperatures [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…forests has been reported in the Mediterranean Sea over the past few decades [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. These declines result from both direct anthropogenic pressures, such as water quality decrease and habitat destruction [ 21 , 22 , 23 , 24 , 25 ], and indirect anthropogenic pressures, such as climate change through global warming and ocean acidification [ 26 , 27 ] and overgrazing by herbivores (mainly in the southeast basin due to biological invasions of rabbitfish or trophic cascades caused by overfishing that lead to an increase in sea urchin populations) [ 28 , 29 , 30 , 31 ]. It is essential to prioritize effective management actions to halt the loss of Mediterranean marine forests and conserve these keystone rocky reef habitats.…”
Section: Introductionmentioning
confidence: 99%